The Bloomsbury companion to Hindu studies - Frazier, Jessica, 1975- (London ; New York : Bloomsbury, 2014)
"Originally published as The Continuum Companion to Hindu Studies, this Companion offers the definitive guide to Hinduism and study in this area. Now available in paperback, The Bloomsbury Companion to Hindu Studies covers all the most pressing and important themes and categories in the field - areas that have continued to attract interest historically as well as topics that have emerged more recently as active areas of research. Specially commissioned essays from an international team of experts reveal where important work continues to be done in the field and, valuably, how the various topics intersect through detailed reading paths. Featuring a series of indispensible research tools, including a detailed list of resources, chronology and diagrams summarizing content, this is the essential tool for anyone working in Hindu Studies"--
"Featuring chapters by an international team of leading scholars in the field, this is a comprehensive reference guide to Hindu Studies"--
Machine generated contents note: -- Foreword Gavin FordList of ContributorsPreface and IntroductionPart I: Introduction: New Visions of HinduismPart II: Key Themes: Reading PathsPart III: The History of Hindu StudiesPart IV: Current Approaches: Articles on Key Themes1. Hindu Cosmology, Angelika Malinar2. Ascetic Traditions, Sondra Hausner3. Tantric Traditions, Dominic Goodall and Harunaga Isaacson4. Bhakti Traditions, Karen Prentiss Pechilis5. Hindu Epics, Simon Brodbeck6. Yoga and Samkhya, Knut Axel JacobsenPhilosophical Traditions, David Lawrence7. Hindu Society, Marie Lecomte-Tilouine8. Hindu Visual Culture, Kenneth Valpey9. Colonial Hinduism, Brian Hatcher]Part V: Regional Perspectives: Local TraditionsPart VI: Research Methods: From Manuscripts to FieldworkPart VII: Future Directions: Issues and DebatesPart VIII: Study Resources: Reading Lists, Sites and SourcesBibliographyIndex.
Reprint: Originally published as The Continuum Companion to Hindu Studies. London : Continuum, 2011.
Includes bibliographical references and index.
Keywords: Hinduism -- Study and teaching; RELIGION / Hinduism / General; RELIGION / General